Pengaturan tentang Kewajiban Pembacaan Akta Oleh Notaris Kepada Penghadap Tuna Rungu - Umar Hasan; Syamsir; Muhammad Kaisar Irsandy Arfa (CV Rewang Rencang, 2024)
Arrangements on the Obligation to Read Deed by Notaries to Deaf Client and to find out and analyze future Arrangements on Procedures for Reading Deed by Notaries to Deaf Client. Normative juridical is